2021
DOI: 10.5194/esurf-9-205-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating optically stimulated luminescence rock surface exposure dating as a novel approach for reconstructing coastal boulder movement on decadal to centennial timescales

Abstract: Abstract. Wave-transported boulders represent important records of storm and tsunami impact over geological timescales. Their use for hazard assessment requires chronological information on their displacement that in many cases cannot be achieved by established dating approaches. To fill this gap, this study investigated, for the first time, the potential of optically stimulated luminescence rock surface exposure dating (OSL-RSED) for estimating cliff-detachment ages of wave-transported coastal boulders. The a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Beyond this, it is possible that the MET-pIRIR protocol may be useful in identifying complex burial or exposure histories of rocks, similar to those that have been reported in previous studies but solely using the IR 50 signal (e.g. Freiesleben et al, 2015;Brill et al, 2021). There is also potential to explore whether the different temperature IRSL signals of the MET protocol record different states of erosion (i.e.…”
Section: Apparent Exposure Ages and Erosion Ratesmentioning
confidence: 75%
See 2 more Smart Citations
“…Beyond this, it is possible that the MET-pIRIR protocol may be useful in identifying complex burial or exposure histories of rocks, similar to those that have been reported in previous studies but solely using the IR 50 signal (e.g. Freiesleben et al, 2015;Brill et al, 2021). There is also potential to explore whether the different temperature IRSL signals of the MET protocol record different states of erosion (i.e.…”
Section: Apparent Exposure Ages and Erosion Ratesmentioning
confidence: 75%
“…Studies have applied rock luminescence techniques (mostly exposure dating) to a variety of lithologies including granites, gneisses (Lehmann et al, 2018(Lehmann et al, , 2019aMeyer et al, 2018), sandstones (Sohbati et al, 2012b;Chapot et al, 2012;Pederson et al, 2014), quartzites (Gliganic et al, 2019) and carbonate limestone (Brill et al, 2021). These studies showed that µ is highly dependent upon the rock lithology, where mineralogy has a strong control on the rock transparency.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prominent methods have recently been used to date the boulder dynamics in medium-low latitudes. Oliveira et al [92] applied lichenometry techniques to date boulder movement on the western coast of Portugal, while Brill et al [93] used optically stimulated luminescence on CBDs located on the Moroccan Atlantic coast, both with encouraging results.…”
Section: The Suitability Of Rocky Coasts As Storm Archivesmentioning
confidence: 99%
“…The interaction of the different scientific disciplines involved in the study of CBDs as natural archives for intense storms is the final point discussed here. Assuming that the identification of suitable CBDs is geomorphological expertise, the contribution of atmospheric physicists, physical oceanographers, hydrodynamics researchers, and other natural science scholars is crucial to establishing the processes that determined their formation (see, e.g., [8,17,21,92,93]). While the intrinsically interdisciplinary nature of such a field of research is strongly emerging, it is necessary to ensure that disciplinary differences do not hinder interdisciplinary research efforts (Sections 1 and 2).…”
Section: The Interdisciplinary Research Perspectivesmentioning
confidence: 99%